THE EFFECTS OF RANDOMIZED DISTRIBUTION OF VEHICLES STOPS ON FUEL CONSUMPTION AND ENVIRONMENTAL POLLUTION: UNIVERSITY CAMPUS CASE STUDY - Raho, Ghazi Ibrahem; Al-Ani, Muzhir Shaban (European Scientific Journal, ESJ, 2014)
Traffic congestions around the world are becoming major nuisances due to the huge number of cars travelling through the streets. The effects of traffic congestion are concentrated on fuel consumption and environmental pollution. This work is concentrated on the study of the effects of randomized distribution of vehicles stops on fuel consumption and environmental pollution. This case study was conducted at a university campus were12 stops situated randomly around the university campus. It is clear that the optimal fuel consumption occurs at speeds 50-80 km/h, and from the study (according to stops situations) it is difficult to reach these speeds. The results of this study showed the location and number of vehicle stops had major effects on amount of fuel consumption and environmental pollutions.